Two efficient and low-complexity iterative reliability-based majority-logic decoding algorithms for LDPC codes - Qin Huang; Jingyu Kang; Li Zhang; Shu Lin; Abdel-Ghaffar, K. (2009 IEEE Information Theory Workshop, 2009)
This paper presents two novel iterative reliability-based majority-logic algorithms for decoding LDPC codes. Both algorithms are binary message-passing algorithms and require only logical operations and integer additions. Consequently, they can be implemented with simple combinational logic circuits. They either outperform or perform just well as the existing weighted bit-flipping or other reliability-based decoding algorithms for LDPC codes in error performance with a faster rate of decoding convergence and less decoding complexity. Compared to the sum-product algorithm for LDPC codes, they offer effective trade-offs between performance and decoding complexity.